Estudo sobre a potencialidade melancólica na clínica infantil - Pires, Gabriela Dias (2007)
This research was developed from the clinical study of an eight year old child, Rodrigo, who is now eleven years old and still being treated. I suppose he is establishing a melancholic potential. The objective of this paper is to understand the identity disorder of this subject starting from the clinical manifestations of some melancholic features and its libidinal and identity history. These features appear during treatment sessions and reveal how Rodrigo s I searches for identity references to reconstruct his history. The methodology used in this work is psychoanalysis, as a theory of the psyche, investigative method of the unconscious and therapeutic technique